Primary aldosteronism-associated cardiomyopathy: Clinical-pathologic impact of aldosterone normalization. (1st October 2019) - Frustaci, Andrea; Letizia, Claudio; Verardo, Romina; Grande, Claudia; Francone, Marco; Sansone, Luigi; Russo, Matteo Antonio; Chimenti, Cristina
Abstract: Background: Primary aldosteronism (PA) causes a cardiomyopathy (CM) which substrate and evolution after aldosterone normalization are unreported. Methods: Four male patients with aldosterone-secreting adrenal adenoma and cardiomyopathy (PACM, group A) were evaluated with 2D-echo, Magnetic Resonance (CMR), coronary angiography and left ventricular endomyocardial biopsy. Biopsy samples were processed for histology, electron microscopy, immunohistochemistry, and Western Blot analysis of myocardial aldosterone receptors and aquaporin 1 and 4. Results were compared with endomyocardial samples from 5 patients with hypertensive cardiomyopathy of equivalent severity and normal plasma aldosterone (group B) and surgical samples from 5 controls (group C). One PACM patient was re-examined with CMR and endomyocardial biopsy 12 months after adrenalectomy with aldosterone and cardiac normalization. Results: Coronary arteries were normal in all. Group A showed prominent myocardial hypertrophy and fibrosis, with water accumulation in the cytosol and organelles of cardiomyocytes and microvascular smooth muscle cells, associated to reduced myofibril concentration and 2.8-fold increase in myocardial aldosterone receptors and aquaporin 1. At CMR, LGE areas were diffusely present. After aldosterone normalization, cardiomyocyte diameter reduced with disappearance of intracellular vacuoles, recovery of electron-density of cytosol and cell organelles, and myofibrillar content, persisting fibrosis and down-regulation of aldosterone receptors and aquaporin 1 channels. At CMR, myocardial mass reduced with recovery of cardiac contractility. LGE signal remained unchanged. Conclusion: PACM is a reversible entity characterized by over-expression of aldosterone receptors and aquaporin 1. It induces a reversible intracellular water overloading causing impaired cardiomyocyte relaxation, contraction and ultrastructural integrity. Highlights: Primary aldosteronism Cardiomyopathy Endomyocardial biopsy